PSYCHOLOGICAL SAFETY UNDER PRESSURE: THE ROLE OF FINANCIAL STRESS IN ONLINE LENDING BEHAVIOR - Yuarini Wahyu Pertiwi; Amirul Muminin (Adisam Publisher, 2025)
The growing use of online lending services in recent years has led not only to financial consequences but also to increasing psychological pressure among users. One of the affected psychological aspects is psychological safety, defined as an individual’s perception of feeling safe to express problems, concerns, or difficulties without fear of negative judgment or shame. This study aims to examine the relationship between financial stress and psychological safety among individuals who have used online lending platforms. A quantitative correlational design was employed, involving 270 respondents with current or past experience in using online loans. Data analysis was conducted using JASP software. The results revealed a significant negative correlation between financial stress and psychological safety (r = -0.340; p < 0.001), indicating that higher financial stress is associated with lower psychological safety. Additionally, respondents with loan default experiences reported significantly lower psychological safety scores (p = 0.008). Most respondents were classified in the moderate to low category of psychological safety. These findings emphasize that economic stress plays a crucial role in diminishing individuals' sense of psychological safety. Therefore, psychosocial interventions and mental health sensitive policies are urgently needed to address the psychological impact of online lending practices.